A new rDNA clone isolated from Neurospora crassa wild type strain 74A containing all coding regions - M. Verma; B. Ghosh; C. Chambers; R. J. Crouch; S. K. Dutta (Fungal Genetics Reports, 1985)
A new rDNA clone isolated from Neurospora crassa wild type strain 74A containing all coding regions